A beacon in the storm: competencies of healthcare chaplains in the accident and emergency department. Issue 3 (3rd July 2021) - Pater, Robin; Visser, Anja; Smeets, Wim
Abstract: Introduction: In several Dutch hospitals, healthcare chaplains provide care to accompanying persons at the accident and emergency (A&E) department, even though they have not been trained for such a dynamic, high-intensity environment. We therefore examined the competencies they feel they need in this setting. Methods: Interviews were conducted with 14 healthcare chaplains from nine hospitals, and with five A&E nurses from two hospitals. Results: All respondents considered healthcare chaplaincy essential in the A&E department. Our findings support the need for psychosocial and communicative skills, knowledge of mourning processes, flexibility, sensitivity, and reflexivity. Additional competencies included sensitivity to existential concerns, practicing presence, a person-centered approach, medical knowledge, and letting go of a solution-oriented approach. Discussion: The chaplains questioned the sufficiency of their leadership skills, pragmatism, and medical knowledge. To ensure their sustained availability for people in crisis, more systematic efforts are needed with regard to aftercare, evaluation, and self-care on the part of healthcare chaplains.